IMPACT OF EXPORTS AND TRADE TAXES ON INDONESIA'S ECONOMIC GROWTH - Ardias Budi Suryono (Transpublika Publisher, 2024)
This research endeavors to comprehensively investigate the intricate dynamics between the export of goods and services, as well as international trade tax receipts, encompassing import and export duties, and their collective impact on the economic growth trajectory of Indonesia over the period spanning from 1985 to 2019. The study meticulously employs secondary data gleaned from reputable sources such as the World Bank and the Ministry of Finance. Utilizing the robust analytical framework of the Error Correction Model within a linear regression analysis, this research delves into the nuanced relationships and temporal aspects that underscore the interplay between these critical economic variables. The findings of this study unveil compelling insights into the long-term effects of exports, import volumes, and the revenues generated from import and export duties on the overall economic growth of Indonesia. Notably, the research establishes that, over the extended time horizon, these variables exhibit a statistically significant influence on economic growth. However, the short-term dynamics present a nuanced picture, as the study reveals that, in the immediate context, neither exports nor import and export duties manifest a discernible impact on economic growth. In conclusion, this research contributes to the existing body of knowledge by shedding light on the multifaceted relationships between key components of international trade and economic growth in Indonesia. The implications of these findings extend beyond the confines of this specific study, providing valuable insights for policymakers, economists, and stakeholders seeking a deeper understanding of the intricate economic landscape.